Prevalence and correlates of overweight and obesity among under-five children in Egypt - Emmanuel Osei Bonsu; Isaac Yeboah Addo (Frontiers Media S.A., 2022)
BackgroundEvidence suggests that Egypt, a country in North Africa, has a significant number of children at serious risk of excess body weight. Yet, there is a dearth of studies on overweight and obesity among children under 5 years in the country. This study examined the prevalence and correlates of overweight and obesity among under-five children in Egypt.MethodsData were retrieved from the latest (2008 and 2014) Egypt Demographic and Health Surveys (EDHS). A total of 42,568 children under 5 years were included. The prevalence of overweight and obesity was described using proportions whereas the factors associated with the prevalence were examined using logistic regression.ResultsOf the 42,568 children under 5 years, about one in every six (17%) were overweight or obese. Children aged 19-37 months, those with birth weights >4 kg, those given large portions of protein foods (eggs and meat), and those whose mothers were in the rich wealth quintile had significant risks of overweight or obesity.ConclusionOverweight and obesity are highly prevalent among children under 5 years in Egypt. Interventions developed to address these two overnutrition indicators in Egypt need to consider variations in risk factors across age, birth weight, food types and portions, and maternal wealth status.